Development and feasibility testing of an intervention to support active lifestyles in youths with type 1 diabetes—the ActivPals programme: a study protocol. Issue 1 (December 2016) - Mitchell, Fiona; Kirk, Alison; Robertson, Kenneth; Reilly, John
Abstract Background The global incidence of type 1 diabetes is rising, and youths with type 1 diabetes continue to suffer poorer health than peers without diabetes. Evidence suggests youths with type 1 diabetes have physical activity (PA) levels well below the recommendations for health and have high levels of sedentary behaviour. An active lifestyle is therefore recommended to improve health. There is limited research showing effective lifestyle behaviour change in this population; therefore, an evidence gap exists between the need to promote physical activity in type 1 diabetes care and lack of understanding on how to do this. This protocol paper describes a feasibility and pilot study of the ActivPals programme—an intervention to support active lifestyles in youths with type 1 diabetes. Methods/design Key intervention components have been identified from preliminary work (individual and family focus, peer mentoring, technology integration and improved communication and understanding) and are being developed into a pragmatic randomised controlled trial (RCT) supported by recruitment pathways. A steering group of health care professionals and managers will refine the intervention to patient needs. A pilot trial is providing data on intervention implementation, acceptability and feasibility. Twenty youths with type 1 diabetes are being recruited and randomised into an intervention or control group. Physical activity is being measured objectively using the Actigraph GT3X+ monitor at baseline and 1-month follow-up. Contextual factors associated with intervention delivery are being explored. Discussion This study will contribute to the development of evidence-based, user-informed and pragmatic interventions leading to healthier lifestyles in youths with type 1 diabetes.